Analysis of the influence of the level of adherence to the ABNT NBR ISO 9001 Quality Management System on the management of the maintenance of defibrillators within a public health care establishment of reference in the specialty of cardiology - Suiane Moraes Machado; Ricardo Kropf Santos Fermam (Revista Sustinere, 2026)
The occurrence of adverse events and technical complaints related to medical equipment (ME) are considered one of the biggest problems in the health area internationally. In Brazil, these technologies are subject to health surveillance. Defibrillators are high-risk ME, which can cause harm to users or lead patients to death. The unavailability of this equipment in health care facilities (EAS) is critical; thus, managing the maintenance of this equipment is imperative for the safety and effectiveness of patient treatment. Objective: Therefore, this study aimed to analyze the influence of the adherence level of the ISO 9001 quality management system in the maintenance area on the maintenance management of defibrillators within a reference EAS in the specialty of cardiology. Methodology: The method used was the case study and analysis of defibrillator maintenance, from 2019 to 2020, and the performance of an internal audit in the ME maintenance area of the selected EAS against the requirements of the ABNT NBR ISO 9001 standard. Results: The equipment, when compared to each other, did not show equivalence related to the type of maintenance and the time interval defined for them, such as the high occurrence of sequential corrective maintenance and, therefore, it can be concluded that preventive maintenance was not efficient. for these equipment. The findings of the internal audit found that the establishment needs to establish and apply the improvements indicated by the ABNT NBR ISO 9001 standard.